The role of extension and advisory services in building resilience of smallholder farmers - Davis, Kristin E.; Babu, Suresh Chandra; Blom, Sylvia (International Food Policy Research Institute, 2014)
The assumption underlying this hypothesis is that farmers lack the knowledge, resources, or both to adequately prevent, anticipate, prepare for, cope with, and recover from shocks. Extension and advisory services may be able to rectify this information asymmetry, or knowledge inequality, by providing or facilitating access to a variety of assets.